Barriereausrüstung von Kunststoffen mittels PECVD: Untersuchung zu Wirkmechanismen der Sauerstoff‐ und Wasserdampftransmission. (February 2016) - Dahlmann, Rainer; Hopmann, Christian; Jaritz, Montgomery; Kirchheim, Dennis
Abstract : Effect Mechanisms in PECVD Barrier Coating of Plastics Especially optical transparency as well as very high barrier functionality, preventing the transmission of gas and aroma, qualifies silicon‐oxide as material of choice for thin PECVD‐coatings on plastics. Whereas permeation through plastics can be described by the Arrhenius‐model, there is no universal model for transport mechanisms through single or multilayer PECVD‐coatings. Models that do exist describe diffusion through defects. These models presume that no permeation besides transmission through these defects occurs. Topic of this research is to determine which model fits the experimental data of oxygen‐ and water vapour‐transmission of experimental data. In order to investigate the applicability of different models, single‐ and both‐sided are compared using different layer architectures.